2017
DOI: 10.3892/mmr.2017.6900
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed procyanidin B2 ameliorates hepatic lipid metabolism disorders in db/db mice

Abstract: Diabetes is commonly associated with liver lipid metabolism disorders. AMP-activated protein kinase (AMPK) has a key role in regulating lipid metabolism. Grape seed procyanidin B2 (GSPB2), a natural polyphenol polymer, ameliorates mitochondrial dysfunction and inhibits oxidative stress or apoptosis via AMPK pathways. In the present study, the hypothesis that GSPB2 treatment may ameliorate liver lipid metabolic disorders by activating AMPK and downstream pathways was tested in diabetic mice. Db/m mice were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Procyanidins represent a group of naturally occurring plant polyphenols withpowerful antioxidative properties, and are mainly found in grape seeds, grape skin, and green tea. Several researches have demonstrated the beneficial effects of grape seeds procyanidins on metabolic diseases . Here, we study the anti‐ALD action of a dimer procyanidin (DPC, Figure ), which is composed of catechins linked by a C─O─C bond.…”
Section: Introductionmentioning
confidence: 99%
“…Procyanidins represent a group of naturally occurring plant polyphenols withpowerful antioxidative properties, and are mainly found in grape seeds, grape skin, and green tea. Several researches have demonstrated the beneficial effects of grape seeds procyanidins on metabolic diseases . Here, we study the anti‐ALD action of a dimer procyanidin (DPC, Figure ), which is composed of catechins linked by a C─O─C bond.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, lipid metabolism disorders are considered a serious health problem in the world population, mainly causing obesity, insulin resistance, inflammation, coronary artery disease and type 2 diabetes (Cao, 2014). The main risk factors for these types of diseases are high body mass index, consumption of alcohol and tobacco, lack of physical activity, low fruit and vegetable intake, high saturated fat intake and low in essential fatty acids, and high n-6/n-3 ratio (Yin et al, 2017). In this sense, many international organizations have recommended the daily consumption of essential fatty acids omega 3 and omega 6, as well as a close ratio between them to stimulate brain development and decrease the induction of different types of cancer and metabolic diseases (British Nutrition Foundation, 1992;World Health Organization/FAO, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment also reduced malondialdehyde concentrations and promoted antioxidant enzyme activities (catalase and superoxide dismutase) compared to the vehicle-treated group, which were related to the activation of Nrf2 protein that upregulates antioxidant defences [ 52 ]. Procyanidin B2 supplementation also reduced 4-hydroxynonenal which is a measure of lipid peroxidation by reactive oxygen species [ 53 ] and advanced glycation end products [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, no differences were shown in serum NEFA concentrations between high-fat and groups treated with epicatechin (10 mg/kg), catechin (10 mg/kg), or procyanidin B2 (10 mg/kg) except those treated with the combination as cocoa powder (100 mg/kg) [ 64 ]. However, administration of 30 mg/kg/day of grape seed procyanidin B2 in diabetic db / db mice reduced body weight [ 53 ].…”
Section: Discussionmentioning
confidence: 99%